SEMIOTIKA ROLAND BARTHES PADA IKLAN WHOOSH “LIBURAN KE BANDUNG ATAU JAKARTA” - Shadavah, Malechha Mutyoro Ichanti; Priatna, Wahyu Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to deconstruct the visual communication strategy and meaning construction behind the Whoosh advertisement video "Liburan ke Bandung atau Jakarta" produced by PT Kereta Cepat Indonesia China (KCIC). Utilizing a descriptive qualitative approach, this research combines Roland Barthes' semiotic text analysis (denotation, connotation, myth) with a contextual framing analysis of corporate social media from the communicator's perspective. Primary data were gathered through the audiovisual scene corpus of the advertisement and an in-depth interview with the Manager of Corporate Communication at PT KCIC. The results indicate that the Whoosh advertisement deliberately sidelining the technical velocity features (350 km/h) and shifts its framing focus toward the aspects of "possibility" and a dynamic, comfortable, and efficient urban lifestyle. Semiotically, the advertisement produces the myth of "the annihilation of space and time," positioning Whoosh as the ultimate solution of modernity over conventional transportation. In the social media sphere, the corporation implemented a re-framing strategy in 2024 by utilizing a cinematic "flat" format to adapt to macro-trends to boost digital engagement. However, this study uncovers a structural dilemma within the corporate communication division regarding the balance between content that triggers digital interaction (engagement) and the commercial urgency of ticket sales conversion (sales).